THE INDONESIAN PROCEDURE TEXT LEARNING THEMED ETHNOBOTANY TO DEVELOP ENVIROMENTAL AWARENESS - Ahmad Syukron; Arief Rijadi (Pancaran Pendidikan, 2023)
Indonesian language learning design innovations need to be continuously prepared to face the challenges of global developments. The Indonesian language subject is the right vehicle for presenting content-based learning because it is text-based learning. Environmental Awareness is an attitude in the form of awareness to think scientifically. Attitudes like this really need to be developed in a planned manner in special learning of Indonesian language learning in schools to prepare generations who have the competence to think critically and innovatively in every problem they face. With Content Language Integrated Learning (CLIL), learning Indonesian in schools can be colored with ethnobotany themes with the aim of creating scenarios for developing Environmental Awareness in students.